Evaluasi Kinerja Keuangan Badan Layanan Umum Daerah - Widowati, Tiwi; N.Masdjojo, Gregorius (JURNAL LITBANG KOTA PEKALONGAN, 2025)
The study aims to evaluate the financial performance of the Regional Public Servic Agency (BLUD) at the Puskesmas in Pekalongan City from 2020 to 2022, by assessing the implementation of The Treasury Directorate General Regulation No.PER-11/PB-2021. The focus of the research is on liquidity, efficiency, effectiveness, and financial independence after the Puskesmas transitioned to auto nomous financial management. The approach applied disquantitative analysis through time seriesand comparative techniques on financial statements. The results show variations in liquidity, efficiency, and independence, with challenges in efficiency and asset management. Improvements in financial management are recommended To improve the standard of health services